Losses associated with mortality of cattle and camels during transportation to Oko-Oba abattoir, Lagos State, Nigeria - Ademola A. Ibironke; Cheryl M.E. McCrindle; Taiwo A. Adejuwon; Simeon I.B. Cadmus (PAGEPress Publications, 2010)
Many food animals meant for slaughter arrive at the Agege abattoir and lairage daily to be produced into wholesome meat for human consumption. These animals generally get to the abattoir packed in Lorries and transported over long distances for many days to get to their destinations. Over a period of 36 months (three years), a total of 1179492 cattle and 11403 camels arrived for slaughter at the abattoir for human consumption. Over the same period, 1197 cattle and 27 camels died in the course of transportation due to the stress and inhumane treatment during transport. All the animals that arrived dead in transit had their carcass totally condemned and destroyed resulting in substantial losses to cattle traders, butchers and the general citizenry. Some of the reasons for these mortalities associated with transportation included overcrowding, long transportation without resting, stress, poor access road networks and traders not adhering to minimal space requirement for animal transportation in a bid to increase their profit margins. Failure to address the issue of proper transportation of food animals are likely to lead to more losses of food animals during transportation.